HADIS-HADIS LARANGAN MENIKAHI SAUDARA PERSUSUAN: Studi Ma’an al-Hadith - Muhammad Hasnan Nahar (UIN Siber Syekh Nurjati Cirebon, 2019)
In Islam, milk-relations has a law effect to getting marriage, forbidden to marry anyone who related to milk-relations, either vertical relations from milk-mother, such as mother of milk-mother, children of mother of milk-mother and children of milk-sibling, or horizontal relationship, such as siblings of milk-mother. The similarity between biological children and milk-children is not limited to text meaning but there is wisdom behind it. By using ma'an al-hadith method of Musahadi HAM,Â it can be concluded that the quality of the hadith is sahih lighayrih, it is based on research conducted on some sanad of hadith. Marrying someone from milk-relations is haram and must be obeyed. This law is not temporary, but starts from appearance that hadith until now and the end of time.